METHODS OF DEVELOPING THE CRITICAL THINKING ABILITY OF PRIMARY CLASS STUDENTS THROUGH FAIRY TALES - Jamolova, Mokhigul (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
This article shows that the ways of forming critical thinking by reading fairy tales in primary classes through different methods and their educational and educational importance, and the possibilities of forming competences related to science.